"Haleem's Hen"; A mnemonic for the anatomy of hindfoot structures at the level of sustentaculum tali on coronal T1-weighted magnetic resonance images. (2022) - Haleem, A.; Moritz, B.W.; Hindawi, S.A.; El-Deeb, H.A.; El-Sherif, A.; Alberawi, M.; Haleem, A.M.
Abstract: Magnetic resonance anatomy of the hindfoot as seen at the level of the sustentaculum tali is intricate due to surrounding muscles, tendons, aponeurosis and ligaments. The objective of this work is to provide a mnemonic with illustrative figures to simplify this complex anatomical region on coronal T1-weighted MR images (T1-MRIs). One hundred and twenty-four patients referred for foot and ankle complaints were scanned utilizing standard MRI imaging protocols for depiction of the hindfoot. Only coronal T1-MRIs of the calcaneus at the level of sustentaculum tali of unremarkably reported patients were selected for this work. Upon viewing the calcaneus with the adjacent anatomical structures on coronal T1-MRIs, the overall appearance resembles a "Hen in the Nest with Four Eggs''. The calcaneus represents the body of the hen, while the sustentaculum tali forms the head and neck. The posterior tibial tendon represents the crest of the hen, and the flexor digitorum longus and flexor hallucis longus tendons represent its beak and wattle, respectively. The peroneus brevis and peroneus longus tendons represent the tail, and the long plantar ligament represents the flexed legs of Haleem's hen. The plantar aponeurosis represents the hen's nest. Whereas the abductor hallucis, flexor digitorum brevis, abductor digiti minimi and quadratus plantae muscles are the four eggs. The mnemonic, "Haleem's Hen in the Nest with Four Eggs", serves as a simplified phrase for radiologists and orthopedic surgeons to easily recall the anatomy of the hindfoot when viewing it at the level of the sustentaculum tali on coronal T1-MRIs.